2022
DOI: 10.1186/s12911-022-02047-6
|View full text |Cite
|
Sign up to set email alerts
|

Automatic ovarian tumors recognition system based on ensemble convolutional neural network with ultrasound imaging

Abstract: Background Upon the discovery of ovarian cysts, obstetricians, gynecologists, and ultrasound examiners must address the common clinical challenge of distinguishing between benign and malignant ovarian tumors. Numerous types of ovarian tumors exist, many of which exhibit similar characteristics that increase the ambiguity in clinical diagnosis. Using deep learning technology, we aimed to develop a method that rapidly and accurately assists the different diagnosis of ovarian tumors in ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The study by Gao et al used a large, multicenter, and heterogenous data set, which disclosed that AI-enabled US outperformed an average trained radiologist in discriminat-ing malignant and benign ovarian masses and improved the examiner's accuracy [189]. These findings were consistent with other studies [185,186], but there were also studies with smaller sample sizes that showed a level of performance reaching those of human experts [188,191,192].…”
Section: Adnexal Massessupporting
confidence: 60%
See 3 more Smart Citations
“…The study by Gao et al used a large, multicenter, and heterogenous data set, which disclosed that AI-enabled US outperformed an average trained radiologist in discriminat-ing malignant and benign ovarian masses and improved the examiner's accuracy [189]. These findings were consistent with other studies [185,186], but there were also studies with smaller sample sizes that showed a level of performance reaching those of human experts [188,191,192].…”
Section: Adnexal Massessupporting
confidence: 60%
“…Of the 11 extracted articles, only two were designed as prospective studies [184,185]. Included studies were published from 2009-2023, whereby the research group Amor et al was the first to describe AI application in sonographic assessment using a non-specified pattern recognition analysis to classify adnexal masses in a new reporting system [184].…”
Section: Adnexal Massesmentioning
confidence: 99%
See 2 more Smart Citations
“…To address these problems, ensembles of DL models (a.k.a. deep ensembles) have been used to overcome the weakness of an individual model [28][29][30]. Ensemble methods combine the prediction of independent models using averaging or majority voting.…”
Section: Introductionmentioning
confidence: 99%